Tailors' Candlesticks (Proceedings of the Society of Antiquaries of Scotland, 1852)
James T. Gibson Craig exhibited two candlesticks from the 17th century, which had been modeled after a Roman altar. The better preserved of the two had the initals I.A. and the year 1634 carved into it. They were found in a house in Dalkeith. Later, the Rev. Alex Mackenzie demonstrated the influence of the Ancient Celts on modern Argyllshire by deriving contemporary proper names from titles for ecclesiastical ofices in the Celtic tradition.